Hepatoprotective Effects of Aqueous Extract of Opilia celtidifolia (Opiliaceae) Leaves against Ethanol-Induced Liver Damage in Rats. (24th October 2020) - Amang, A. P.; Kodji, E.; Mezui, C.; Baane, M. P.; Siwe, G. T.; Kuissu, T. M.; Emakoua, J.; Tan, P. V.
Abstract : Objective . Opilia celtidifolia is a plant used in Cameroonian ethnomedicine to cure jaundice. The aim of this study was to evaluate the hepatoprotective activity of O. celtidifolia leaves aqueous extract in rats subjected to ethanol-induced liver damage. Material and Methods . 36 rats including 18 males and 18 females were divided into 6 groups of 3 males and 3 females each, namely, 3 control groups (normal, negative, positive) and 3 test groups. The normal and negative control groups were given distilled water (5 ml/kg), the positive control group received silymarin (100 mg/kg), and the test groups were given O. celtidifolia extract at the doses of 100, 200, and 400 mg/kg. All groups, except the normal control, received concomitantly and daily 40% ethanol (4 g/kg) for 3 weeks to induce hepatotoxicity. Biochemical parameters such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), bilirubin, and lipid profile (total cholesterol, HDL, LDL, and triglycerides) were evaluated. Histological sections of the liver, kidneys, and lungs were examined. Qualitative and quantitative phytochemical analysis of the extract were carried out. Results . The groups treated with the extract at the doses of 200 and 400 mg/kg showed a significant decrease (p < 0.001 ) of transaminases (ALT and AST), ALP, and bilirubin compared with the negative control. These results were confirmed by observation of histological sections of the liver that confirmed protective action of extract against ethanol-induced hepatocellular injury. Conclusion . O. celtidifolia possesses hepatoprotective properties that could be related to its high content of tannins and saponins in the leaves aqueous extract.